Delphi method to identify expert opinion to support children's cancer referral guidelines. Issue 3 (16th August 2019) - Murray, Matthew J; Ruffle, Amy; Lowis, Stephen; Howell, Lisa; Shanmugavadivel, Dhurgshaarna; Dommett, Rachel; Gamble, Ashley; Shenton, Geoff; Nicholson, James
Abstract : Background: The National Institute for Health and Care Excellence (NICE) guidance for referral of children with suspected cancer was first published in 2005 and updated in 2015. The updated version relied on sparse primary care evidence and published without input from key stakeholders, for example, acute general paediatricians and paediatric haematologists/oncologists. This led to a document that fell short as a practical guide for referring physicians managing children with potentially life-threatening conditions. Following discussions between the Children's Cancer and Leukaemia Group (CCLG, the UK multidisciplinary professional body for healthcare professionals caring for children with cancer) and NICE, it was agreed that a practical supplement should be produced for the 2015 guidance. A prerequisite was evidence gathering from tertiary care to balance the existing primary care evidence, and a Delphi consensus method was therefore convened. Methods: A CCLG NICE Guidance Committee formulated 25 draft statements for review. The CCLG emailed its paediatric haematologist/oncologist membership (n=179) and 88 responded (49%). To achieve consensus, statements required ≥70% agreement from ≥60% of actual respondents, from the denominator (n=88). Results: Fifteen of 25 original statements were accepted at the first round of voting. Three of 25 statements where >50% did not support were rejected outright. One statement could not be revised without replicating a previously accepted statement. The six remaining statements were revised and a second round of voting undertaken; all six revised statements were accepted. Overall, 21 of 25 statements (84%) met consensus criteria. Conclusions: This expert opinion should help streamline suspected cancer referral in children and help optimise subsequent outcomes.